TEACHERS` PERCEPTIONS OF DIGITAL GAME-BASED VOCABULARY LEARNING - Poppy Shania M. Sihombing; Anna Riana Suryanti Tambunan (LINGUISTIK TERAPAN, 2023)
The most problem in teaching and learning English that faced by the teacher is the students` lacks of vocabulary. The problem caused by the media used in teaching and learning process that makes the students feel bored, less motivation when joining the class. So, it needs the novelty learning media especially in teaching vocabulary, such as: Digital Game-Based Vocabulary Learning (DGBVL). This study investigates how the elementary EFL teachers` perceptions of DGBVL. It is used the qualitative research method with a case study design. 3 EFL teachers who work in Ulul Ilmi elementary school in Medan were interviewed. Data collected through interviews was analyzed using the descriptive analysis method. The study's findings indicated that teachers have generally positive perceptions of DGBVL. For the appropriateness, it was very good, appropriate for use as a learning media, can create an effective, creative, innovative, and fun learning process. For the content, teachers expressed their perception that in general, the content was sufficient, although it may be simplified more and that it was transferable to students. For the assessment, teachers expressed generally positive about the assessment as it was based on implementation. Teacher revealed that the biggest problem was time constraints, some students were still unable to operate DGBVL